Pengembangan UMKM Berbasis Potensi Lokal melalui Sinergi Pemasaran Inovatif dan Kebijakan Desa - Khoyrul Anwar; Puspita Dewi, Sangrila; Wijayanti Mala, Istiana (Universitas Dr. Soetomo Surabaya, 2026)
The development of micro, small, and medium enterprises (MSMEs) based on local potential is a key strategy for fostering sustainable rural economic growth. Karanggupito Village in Ngawi Regency possesses distinctive local potential in the form of durian products, which offer strong prospects for value-added MSME development. However, at the initial stage, this potential had not been fully transformed into a source of competitive advantage, as it was primarily treated as raw material and insufficiently integrated into marketing strategies and product identity. This study examines the development of local potential–based MSMEs through the synergy between innovative marketing strategies and village development policies. Employing a qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis. The findings show that digitally driven marketing innovations—particularly the use of social media and e-commerce platforms—enhance marketing capabilities, expand market reach, and strengthen branding grounded in local identity. Importantly, this study contributes novel empirical insights by proposing an integrative village-level framework that links local resource-based marketing innovation with village development policies as mutually reinforcing mechanisms. The effectiveness of marketing innovation is shown to be highly dependent on sustained policy support, including access to capital, capacity building, collective promotion, and institutional collaboration. This research highlights that MSME development in rural contexts cannot rely solely on entrepreneurial initiatives but requires policy-enabled innovation ecosystems to convert local potential into sustainable competitive advantage and long-term rural economic resilience.